Cassava improvement in the era of "agrigenomics": the road to nextgeneration breeding. - Rabbi, Ismail Y.; Gedil, Melaku A; Ferguson, Morag E.; Kulakow, Peter A. (2012)
In the last 45 years, IITA has played a pivotal role in the genetic improvement of cassava for resourcepoor farmers in sub-Saharan Africa (SSA). More than 400 varieties have been developed that are not only high yielding but also resistant to diseases and pests. Many of these improved varieties have been extensively deployed in SSA and have helped to avert humanitarian crises caused by the viral disease pandemics that devastated local landraces in East and Central Africa.